Team Approach: Treatment of Diabetic Foot Ulcer. Issue 7 (26th July 2016) - Pinzur, Michael S.; Cavanah Dart, Harriet; Hershberger, Richard C.; Lomasney, Laurie M.; O'Keefe, Paul; Slade, David H.
Abstract : At any point in time, 3% to 4% of the 29.1 million diabetic patients in the United States (9.3% of the population) will have a foot ulcer. Diabetes-associated foot ulcers and infection lead to >70, 000 lower-extremity amputations yearly in the United States. Between one-third and one-half of diabetic patients undergoing a major lower-extremity amputation will die within 2 years after the amputation. Multidisciplinary population health-management strategies have been developed to decrease the rate and magnitude of this important comorbidity in the diabetic population. The goal of the present review is to provide the reader with a framework for the development of a health-care-system strategy for addressing this complex patient population.